Hábitos de leitura dos estudantes de jornalismo : estudo do comportamento dos nativos digitais - Marchesan, Isabel (2016)
This study, of an exploratory nature, aims to show what the future professional journalists read and how they feed themselves information about past and present history. Through a survey, 52 journalism students, from three different universities in Rio Grande do Sul (UFRGS, Unisinos and UFSM) were interviewed. Most of them are youngsters who grew up surrounded and using digital gadgets and the internet: they are part of the digital native generation. The students answered a questionnaire about their reading habits regarding books and journals (newspapers and magazines); how they use internet and how social media influences the way they read and keep up to date with the news. Their answers were quantified and compared to other studies from around the world. These results allow some insights: university and professors have very little influence on what these students choose to read, and reading books is mainly a recreational habit, not motivated by academic needs. It is also possible to deduce that book reading is analogical, in paper, while newspapers and magazines are digital, because most of the students read them online, in their computers. The analysis of the answers is followed by a discussion on the future of reading: how do this generation consume news, and what impacts, good or bad ones, do digital technologies have and will have on the way they access, use and store information and culture.